Given parameters:
Quadratic expression:
x² - 6x + 7 = 0
Solve using quadratic formula;
x = ![\frac{-b +/- \sqrt{b^{2 } - 4ac} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%20%2B%2F-%20%5Csqrt%7Bb%5E%7B2%20%7D%20-%204ac%7D%20%7D%7B2a%7D)
From the equation;
a = 1, b = -6 and c = 7
Input the parameters and solve;
x = ![\frac{-(-6) +/- \sqrt{-6^{2 } + 4 x 1 x 7 } }{2 x 1}](https://tex.z-dn.net/?f=%5Cfrac%7B-%28-6%29%20%2B%2F-%20%5Csqrt%7B-6%5E%7B2%20%7D%20%2B%204%20x%201%20x%207%20%7D%20%7D%7B2%20x%201%7D)
x = ![\frac{6 +/- \sqrt{36} +28 }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%20%2B%2F-%20%5Csqrt%7B36%7D%20%2B28%20%7D%7B2%7D)
x = ![\frac{6 +/- \sqrt{64} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%20%2B%2F-%20%5Csqrt%7B64%7D%20%7D%7B2%7D)
x =
or ![\frac{6-8}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6-8%7D%7B2%7D)
x = 7 or -1
Answer:
Step-by-step explanation:
3
In the sequence, the numbers are going down by -3. So the nth term must start with -3n. To get from -3 to 4 you must add 7. This makes the nth term -3n+7.